Sternal Fractures: Emergency Management and Radiologic Evaluation - ALmarshad, Basim Othman Naser; Osama Saud Albulayhid; Yousef Shammat Suwayyid Alanazi; Nasser Abdialeaziz Ahmad Alkhamis; Khalid Abdullah Alkhaldi‏ ‏; Yahya Abdulrahman Y Dhamiri; Mahmood Mansour Saeed Alzaid‏ ‏; Abdulrhman Hamad ALsarrani; Mohammed Hamad ALqahtani; Yousef Ali Atiaha Alnahwi; Mohammad Ibrahim Mohammad ALnefisa; Ahmad Mohammed Saleh Aljuaythin (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Sternal fractures are uncommon but clinically important injuries that typically result from blunt anterior chest trauma, most often associated with high-energy deceleration events such as motor vehicle collisions. Although once considered markers of severe trauma, advances in imaging and trauma care have improved their detection and management. The main clinical concern lies in the high frequency of associated thoracic, pulmonary, and cardiac injuries rather than the fracture itself. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article aims to review the etiology, epidemiology, pathophysiology, clinical presentation, diagnostic strategies, and management approaches of sternal fractures in the emergency setting, with an emphasis on radiologic evaluation and multidisciplinary care. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A narrative review approach was used, synthesizing current evidence from trauma and emergency medicine literature. The discussion integrates clinical assessment, imaging modalities—including radiography, computed tomography, and ultrasound—and principles of emergency and trauma management guided by Advanced Trauma Life Support protocols. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Sternal fractures most frequently result from blunt trauma, particularly motor vehicle collisions, but may also arise from insufficiency or stress mechanisms. Lateral chest radiographs and computed tomography are critical for diagnosis, while cardiac monitoring and biomarkers are essential to detect associated myocardial injury. Most isolated fractures are managed conservatively with analgesia and respiratory support, whereas surgical fixation is reserved for displaced or unstable injuries. Prognosis is generally favorable in isolated cases but worsens significantly with associated injuries. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Sternal fractures require systematic evaluation due to their strong association with life-threatening thoracic injuries. Early diagnosis, appropriate imaging, and multidisciplinary management are key to optimizing outcomes.